Impact of Chlorine and Heat on the Survival of Hartmannella vermiformis and Subsequent Growth of Legionella pneumophila - Kuchta, John M. (1993)
Hartmannella vermiformis, a common amoebal inhabitant of potable-water systems, supports intracellular multiplication of Legionella pneumophila and is probably important in the transportation and amplification of legionellae within these systems. To provide a practical guide for decontamination of potable-water systems, we assessed the chlorine and heat resistance of H. vermiformis. H. vermiformis cysts and trophozoites were treated independently with chlorine at concentrations of 2.0 to 10.0 ppm for 30 min and then cocultured with L. pneumophila. Both cysts and trophozoites were sensitive to concentrations between 2.0 and 4.0 ppm and above (trophozoites somewhat more so than cysts), and 10.0 ppm was lethal to both forms. Hartmannellae treated with chlorine up to a concentration of 4.0 ppm supported the growth of legionellae. To determine whether heat would be an effective addendum to chlorine treatment of amoebae, hartmannellae were subjected to temperatures of 55 and 60°C for 30 min and alternatively to 50°C followed by treatment with chlorine at a concentration of 2 ppm. Fewer than 0.05% of the amoebae survived treatment at 55°C, and there were no survivors at 60°C. Pretreatment at 50°C appeared to make hartmannella cysts more susceptible to chlorine but did not further reduce the concentration of trophozoites.